ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN SISTEM INFORMASI AKADEMIK KHUSUS ORANG TUA - Bashir, Nur Azmi Ainul; Dirgahayu, Teduh (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
This time, parent's academic information system service or SIORTU is often found on several campuses. One of the campuses that provides this system is Islam Indonesia University. This system made for helping parents of students to monitor their children's academic activities. Until now, many parent of student who have not used this system. There are 20.068 SIORTU accounts provided for parents of students from 2015 to 2018. But, only 7.361 or 36,68% account who active between April 2018 and Maret 2019. This research discusses factors that influence to use siorto and why these factors are included. Expectations of this research, gave feedback to owner of SIORTU service to improve that system, provide references for future research and provide references for educational institution. So that, SIORTU can be use as expected. This research is a quantitative research, which is done by analyzing the data in the form of voting from 75 respondents. The research respondent is parent of student from Islam Indonesia University who have used this system from April 2018 to March 2019. The software who they use to analyze is SmartPLS 3 by Partial Least Squares (PLS) method. The result of analysis who obtained was pointing that factors that influence this system are social influence, facilitating condition, habit, behavioral intention. These factors are evidence from the result of the analysis which show a positive value on original sample estimate and significant value on T statistic.